Analysis of Anxiety and Self-Efficacy on Athlete Performance in Pencak Silat CompetitionsAnalysis of Anxiety and Self-Efficacy on Athlete Performance in Pencak Silat Competitions - Widorotama, Angger; rahayu, tandiyo; setiawan, ipang; pambudi, yudhi teguh (Journal of Physical Education and Sports, 2024)
Several factors affect peak performance for athletes and include match anxiety and self-efficacy. The purpose of this study was to determine the analysis of competition anxiety and self-efficacy on athletes' peak performance in pencak silat matches. This study uses a mixed methods design to provide analyses related to competition anxiety, self-efficacy and peak performance in athletes in pencak silat competitions. The research subjects were taken using puposive sampling technique involving 42 teenage pencak silat athletes at regional student sports week District Level who came from Public Vocasional School 3 Purwokerto, Public Islamic Senior High School Purbalingga, Vocational School Muhamadiyah Bobotsari, Public Senior High School 2 Purbalingga and Islamic Integrated Senior High School Nurul Ihsan. Data were obtained through questionnaires on competition anxiety, self-efficacy and peak performance. Qualitative data analysis involves collecting, presenting, and drawing conclusions while quantitative data analysis uses Rank Spearman data analysis techniques. The results showed that the relationship or correlation of anxiety competing with peak performance got a correlation coefficient of 0.701, while the relationship or correlation of self-efficacy with peak performance got a greater correlation coefficient of 0.830. So the hypothesis that states there is a relationship between competition anxiety and self-efficacy with peak performance of martial arts athletes is accepted. Conclusion: (1) Based on the results of the correlation coefficient value obtained, it can be interpreted that the two variables have very strong relationship results. (2) The correlation coefficient value of self-efficacy is greater than the anxiety of competing, meaning that the self-efficacy variable is more influential on the peak performance of athletes in pencak silat matches compared to the variable anxiety of competing.